1984
DOI: 10.1115/1.3239545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pin Shape and Array Orientation on Heat Transfer and Pressure Loss in Pin Fin Arrays

Abstract: Modern high-performance gas turbine engines operate at high turbine inlet temperatures and require internal convection cooling of many of the components exposed to the hot gas flow. Cooling air is supplied from the engine compressor at a cost to cycle performance and a design goal is to provide necessary cooling with the minimum required cooling air flow. In conjunction with this objective, two families of pin fin array geometries which have potential for improving airfoil internal cooling performance were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(95 citation statements)
references
References 0 publications
6
88
1
Order By: Relevance
“…Recently, [16], using a "lumped heat capacity method" for the pin fins, reported an inverse result; they mesured a higher HTC over the endwall by about 3-40% than that on the corresponding pin fin of the same row. Figures 7 and 8 present all the experimental data in the two different definitions of Reynolds and Nusselt number reported in (1) and (2).…”
Section: Experimental Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, [16], using a "lumped heat capacity method" for the pin fins, reported an inverse result; they mesured a higher HTC over the endwall by about 3-40% than that on the corresponding pin fin of the same row. Figures 7 and 8 present all the experimental data in the two different definitions of Reynolds and Nusselt number reported in (1) and (2).…”
Section: Experimental Uncertaintymentioning
confidence: 99%
“…Being easier to manufacture, pin fins with circular cross-sections are the most used and investigated. The first experimental investigations on circular pin fins were carried out by [1][2][3]. They measured row by row heat transfer coefficients and pressure losses for inline and staggered configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Metzger, et al [11] reported the effect of flow incident angle on oblong pins. All incident angles except 90° yield higher Nusselt numbers than circular pins.…”
Section: Effect Of Pin Shape and Array Orientationmentioning
confidence: 99%
“…Metzger et al [16] investigated the effects of pin-edge shape and show presentation on the glow trade and the weight incident in pin-equalization bunches. They demonstrated by their results that the use of round and empty pin-parities with a group introduction amongst astonished and in-line can now and again propel the glow trade, while fundamentally decreasing weight.…”
Section: Introductionmentioning
confidence: 99%